Práticas educativas no ensino de ciências no Bosque Municipal Jary Antônio Linck – Tenente Portela/RS - Wollmann, Tiago (2023)
The existing green areas in urban spaces become increasingly limited, it is necessary to take advantage of these environments for the development of educational practices in these non-formal teaching spaces. The present research in the Municipal Forest Jary Antônio Linck de Tenente Portela - RS, arises from the need to value this environment as a strategy for the development of scientific knowledge, creating in students the bonds with nature, reinforcing the social role of this public space, stimulating the feeling of belonging in relation to this urban green area. The environment in its context creates stimuli that permeate many sensations and learning, favoring the development of innovative practices, using it as a didactic resource to bring the contents closer to the concepts worked, relating it to the thematic units of the National Common Curricular Base. The objective of the research is to analyze possibilities of using an urban green area for the development and improvement of educational practices in science teaching. The research focuses on the students of the 5th grade, of a Municipal School of Elementary Education of Tenente Portela – RS.The proposed methodology is the qualitative nature, type action-research, the teacher, through the teaching practices that develops, seeks to optimize the teaching of Sciences in this context. The research is organized in two chapters and its actions potentiate the Forest as a non-formal space, followed by theoretical assumptions that guide the development of effective educational practices. Among the activities developed in the Forest, the construction of the terrarium was carried out from the collection of materials such as earth, stones, leaves, small plants, allowing to identify and relate the concepts of the levels of organization of the ecosystem; reading environment in Sciences, through readings of the magazine Ciência Hoje and literary books, in order to recognize the Forest as a place that allows the development of reading practices, perfecting vocabulary, sharpening cognitive, creative and writing potential. From the rescue of memories, it was referred to the memories of the activities developed in the forest, allowing the students to remember the experiences through dynamics of representations of drawings and textual production. The data collected indicate that the Forest is a promising environment to develop contextualized practical activities, integrating the school curriculum with important meanings that will be eternalized in the teaching-learning process.